Fernando Pessoa na Boca do Inferno: Dá a surpresa de ver um filme erótico detetivesco - Medeiros, Ana Clara Magalhães de (Pessoa Plural)
This work analyzes the film Boca do Inferno (2020) by Portuguese director Luís Porto, focusing on how the film composition articulates: a) the encounter – and its documented outcome – between the poet Fernando Pessoa, the English magician Aleister Crowley, and his young German lover, Hanni Larissa Jaeger, in September 1930, in the city of Lisbon; b) the poem “Dá a surpresa de ser”, which is part of Pessoa’s orthonymic work. We are interested in providing a critical interpretation of the Mouth of Hell episode that involved Fernando Pessoa in a staged suicide and a hypothetical love triangle, as narrated in the 2020 medium-length film. To do so, we prioritize an analysis of the indices of eroticism emerging from the cinematic production.